The socialization spectrum: Malay students and interethnic engagement - Radzlan, Rohaizahtulamni; Adam Assim, Mohd Ibrani Shahrimin; Rosnon, Mohd Roslan; Abang Abai, Dayang Shobihah (Human Resource Management Academic Research Society, 2025)
Malaysia’s multicultural society offers both challenges and opportunities for fostering interethnic engagement. This study explores the role of socialization among Malay students across three critical domains: family, peers, and media. Within families, cultural incongruence may limit exposure to diverse perspectives, while ethnically homogeneous peer groups often reinforce in-group norms, reducing opportunities for meaningful interethnic interactions. Similarly, biased media narratives can perpetuate stereotypes and hinder inclusive attitudes. These barriers illustrate the complex interplay between socialization domains in shaping Malay students’ attitudes, perceptions, and behaviors toward interethnic relations. By understanding these dynamics, this research sheds light on the factors influencing interethnic engagement and their implications for social cohesion. Addressing these challenges can help foster stronger bonds between ethnic groups, promoting a more inclusive and harmonious society. Ultimately, this study contributes to ongoing efforts to strengthen Malaysia’s social fabric through targeted interventions and policies that enhance interethnic understanding and cooperation.